ASAS EQUITY KENAIKAN TARIF PPN: SEBUAH PERSEPSI - Putra Yasa, I Nyoman; Nyoman Ari Surya Dharmawan; Luh Madori Sekarsari (Vokasi : Jurnal Riset Akuntansi, 2024)
This research aims to reveal the public's perception of equity over the increase in VAT rates which will take effect from early 2025 in accordance with the mandate of Law number 7 of 2021 concerning the harmonization of tax regulations. This research is a qualitative research based on case studies. The informants used are authorities, tax academics who have an understanding of taxation, especially VAT, and business actors who have been registered as taxable entrepreneurs.The results of this study state that there is a fundamental material from the perspective of the authorities, academics and business actors towards the increase in VAT. The authorities said it was natural for VAT to be increased because it is a source of state revenue that has been in need of modernization for 30 years. On the other hand, academics and business actors view that this tariff increase only provides short-term benefits, but will have a long-term impact, especially related to people's purchasing power. In the equity aspect, this increase is seen as reasonable and fair by the authorities, especially when it is associated with state revenue which will later be used for the welfare of the community. However, academics view this justice as pseudo, and can even have an impact on public perception of the authorities.